Development and application of an Integrated Beach Quality Index (BQI). (1st July 2017) - Semeoshenkova, Vera; Newton, Alice; Contin, Andrea; Greggio, Nicolas
Abstract: The quality of beaches is a very important factor for attracting tourists. Continuous improvement of beach quality is an important goal for coastal countries such as Italy, where "beach and sun" tourism is a prominent contributor to the economy. The challenge for beach managers is both to protect the environmental quality of beaches and improve the quality of tourist experience. An integrated Beach Quality Index (BQI) to evaluate "Environmental Quality" and "Human Welfare & Health" was designed. It was applied to three different types of beaches, (urban, semi-urban and semi-rural), on the Adriatic coast. The BQI allowed an assessment of (i) the overall beach quality; (ii) individual aspects of beach quality on three types of beaches; (iii) the main strengths and weaknesses of the study beaches; and (iv) priorities for future management. The overall quality was evaluated as "Excellent" at the Cesenatico Levante – Porto Canale Sud (urban) and Marina di Ravenna (semi-urban) beaches and as "Good" at Bellocchio (semi-rural) beach. However, some of the individual aspects of beach quality had lower values, which show a potential for improvement through onsite management. The composite index is a useful tool for evaluating beach quality and to support the decision making process. It identified possible management responses for improving the beach quality of the study sites to propose to the responsible authorities. Moreover, it can significantly contribute to the development of Beach Management Framework aimed to support an effective management of individual beaches, enhance beach tourism, boost income, and in long term, to support a sustainable development of coastal areas. Highlights: Beach tourism depends on maintaining beach quality. An Integrated Beach Quality Index (BQI) has been developed. The BQI can be applied to different beach types. The "Environmental Quality" and "Human Welfare & Health" were assessed. The BQI allows an identification of management priorities to improve beach quality.